Incidence and impact of antiplatelet therapy cessation among very older patients with stable coronary artery disease - Zou, Xiao; Wang, Liang; Sun, Sha-Sha; Hu, Yi-Xin; Liu, Hong-Wei; Wang, Hao; Cao, Jian; Liu, Hong-Bin; Fan, Li (Frontiers in Pharmacology, 2023)
Objectives: Long-term use of evidence-based antiplatelet therapy is recommended for management of stable coronary artery disease (SCAD). However, non-adherence to antiplatelet drugs is common in elderly patients. This study aimed to evaluate the incidence and impact of antiplatelet therapy cessation on clinical outcomes of elderly patients with SCAD. Methods: A total of 351 consecutive eligible very elderly patients (≥80 years) with SCAD from the PLA General Hospital were included. Baseline demographics, clinical characteristics, and clinical outcomes were collected during follow-up. Based on past experiences of antiplatelet drugs cessation, 140 patients were assigned to the standard group and the remaining 211 patients to the cessation group. The primary outcome was major adverse cardiovascular events (MACE) and secondary outcomes were minor bleeding and all-cause mortality. Results: A total of 351 participants, with a mean age of 91.76 ± 5.01 years old (range 80–106 years) were included in statistical analysis. The antiplatelet drug cessation rate was 60.1%. During a median follow-up of 98.6 months, the primary outcome of MACE occurred in 155 patients (73.5%) in the cessation group and 84 patients (60.0%) in the standard group (HR=1.476, 95% CI:1.124-1.938, P=0.005). Cessation of antiplatelet drugs increased the rates of angina (HR=1.724, 95% CI:1.211-2.453, P=0.002) and non-fatal MI (HR=1.569, 95% CI:1.093-2.251, P=0.014). The secondary outcomes of minor bleeding and all-cause mortality were similar between the two groups. Conclusions: Among very elderly patients with SCAD, antiplatelet therapy cessation significantly increased the risk of MACE, and continuous antiplatelet drug therapy didn’t increase the risk of minor bleeding.